(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Lexicography is the art and science of dictionary-making. It involves the systematic collection, analysis, and organization of words and their meanings, often resulting in the creation of dictionaries or lexicons. Lexicographers study language usage, gather information about word origins (etymology), and document various meanings, pronunciations, and grammatical functions of words. There are two main types of lexicography: descriptive lexicography, which aims to observe and record how language is used in practice without prescribing rules, and prescriptive lexicography, which provides guidelines on correct language usage based on established norms. The work of lexicographers is essential for understanding linguistic evolution, supporting language education, translating texts, and preserving cultural heritage through written records. In recent years, advancements in technology have transformed lexicography with the rise of digital dictionaries and online resources that allow for more dynamic updates and greater accessibility to users worldwide.